A good global investment for the United Kingdom: How investing in CGIAR reduces global poverty and benefits U.K. citizens - Hill, Ruth Vargas; Martin, Will; McNamara, Brian; Nia, Reza; Spielman, David J.; Takeshima, Hiroyuki; Vos, Rob (International Food Policy Research Institute, 2025)
CGIAR investments have delivered substantial economic benefits for the U.K. while reducing global poverty and food insecurity. CGIAR has boosted productivity on British farms, expanded export markets, and made food more affordable for British consumers. It has also helped prevent potential damage from pests and diseases that threaten U.K. farm livelihoods. CGIAR investments are likely to continue benefiting U.K. farmers in the future as the CGIAR’s provision of genetic material to the U.K. has increased over time. This paper quantifies the benefits to farmers, exporters and consumers.